Cutaneous Tuberculosis : Where are we Standing? (Advancements in Homeopathic Research, 2022)
Cutaneous TB is caused by M. tuberculosis in a majority of cases and, rarely, by M. bovis. It accounts for 0.1– 0.9% of the total dermatology out-patients in India.[1,2] The diagnosis of cutaneous TB is based on the characteristic clinical morphology of the lesions as well as laboratory tests. Common clinical differential diagnoses of skin TB include cutaneous leishmaniasis, leprosy, atypical mycobacterial infections, fungal infections like chromomycosis and sporotrichosis and sarcoidosis. Many of these conditions also show granulomas on histology and thus definitive diagnosis relies on the direct demonstration of tubercle AFB on stained smears or biopsies, isolation by culture or detection by PCR and related molecular techniques.
Keywords: Cutaneous TB; tuberculosis; dermatology; AFB; PCR